Post-Covid pain frequency and affecting factors - Tetik, Bora; Demir, Gülsüm Hilal; Kurt, Osman; Derya, Serdar (My University, 2021)
Covid-19 disease was believed to be a short-term disease. However, as the disease was continuing to spread, it was understood that, it can continue for a long time. The aim of this study is to determine the symptoms of individuals with Coronavirus disease 2019 (Covid-19) and those who recovered from the disease and whether they have ongoing symptoms after recovery and the factors affecting of their pain complaints. This descriptive study included 152 patients who admitted to our hospital and diagnosed with Covid-19 and those recovered. The patients were interviewed by telephone and were questioned about their symptoms and conditions when they had Covid-19 and after recovering from Covid-19, by questions based on the literature as well as sociodemographic characteristics. The mean age of the patients was 44.9±13 (min=20, maks=83) and 66 (43.4%) were female and 86 (56.6%) were male. It was determined that 43 patients (28.3%) had and recovered from Covid-19, 1-2 months ago, 60 (39.5%) 2-3 months ago, 36 (23.7%) 3-4 months ago, and 13 (8.8%) 4-5 months ago. During the Covid-19 disease period, pain conditions were listed as 112 had body pain, 94 had headache, 36 had back pain, 35 had joint pain and 13 had lumbar pain. Post-Covid pain was detected in 12 people (7.9%). Body pain was reported in 5 people, headache in 2 people, lumbar pain in 4 people, and both body and joint pain in 1 person. It was observed that as the age group increased, the incidence of post- Covid pain increased. It was determined that the post-Covid pain rate was 7.9% and the patients experienced long-term body, head, lumbar and joint pain. Post-covid pain syndrome was more common in older ages. We suggest that a follow-up algorithm for post-recovery period should be developed.
Keywords: Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri; Psikoloji